Rights of Seafarers and Shore Personnel: Emerging Trends and Ongoing Challenges - Мінченко, Дар'я Анатоліївна; Мінченко, Д. А.; Minchenko, Daria A. (Odesa : Publishing House Helvetica, 2025)
The article explores recent initiatives by international organizations and national governments to protect the rights of seafarers and port workers. Recent developments in seafarers’ labour rights and wellbeing, and their recognition as “key workers” under the 2025 updates to the Maritime Labour Convention, have increased attention to the like rights of port personnel. The discussion emphasizes the European Court of Human Rights’ (ECHR) case law concerning seafarers and its significance in understanding jurisdictional practices and holding States accountable for ship crew mistreatment and environmental violations. Special focus is made on how protecting seafarers’ human rights intersects with the enforcement of environmental policies in the shipping industry.
Minchenko D. Rights of Seafarers and Shore Personnel: Emerging Trends and Ongoing Challenges / D. Minchenko, O. Stets // Lex Portus. – Odesa : Publishing House Helvetica, 2025. – 11(5). - P. 22–30. URL: https://doi.org/10.62821/lp11502
Keywords: maritime industry; shipping; human rights; seafarers; court rulings; ECHR case law; “key workers”; port operations; green transition; environmental rights